Sustainable Livelihoods Analysis as a Response to the Crisis in the Community and Voluntary Sector. (July 2020) - Goldstraw, Katy; Davidson, Eve; Packham, Carol
The aim of this article is to recognize the crisis currently experienced by the voluntary and community sector (VCS) and to consider a creative response to this crisis utilizing VCS assets. The article uses a creative assets based response to the VCS crisis, utilizing sustainable livelihoods' analysis (SLA) as a means of identifying VCS assets. SLA, traditionally used to explore vulnerabilities and assets at a household level, will be expanded and utilized to analyze the effects of austerity on small voluntary organizations. We use SLA as a theoretical lens through which to analyze our data, we propose that small VCS organizations can consider their position using SLA as a tool. The VCS can use SLA to consider its assets and vulnerabilities in the context of austerity; in engaging in this process, the VCS can recognize opportunities. The small VCS organization typically has high-quality community-based social capital, and it has a human capital and community knowledge. This integrated grassroots social capital expertise and strong community-based human capital is unique to the VCS. In mobilizing its assets, the VCS as a sector can seek to overcome the funding crisis that it is experiencing and develop creative solutions to austerity.